2020
DOI: 10.1111/anu.13048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fish and vegetable oil on the growth performance, body composition, fatty acids profile, reproductive performance and larval resistance in pearl gourami (Trichogaster leeri)

Abstract: This study investigated the effect of two lipid sources on reproduction performance and growth in pearl gourami. For this purpose, 180 fish (3.32 ± 0.25 g) were fed with three isoenergetic (19.80) and isonitrogenous diets (480 g/kg protein) including FO (80 g/kg fish oil), FS (40 g/kg fish oil and 40 g/kg soybean oil) and SO (80 g/kg soybean oil) for 10 weeks before maturation. At the end of the trial, there was no significant difference in weight gain, feed conversation ratio and body composition between fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 82 publications
1
16
0
Order By: Relevance
“…All procedures involving animals were performed according to the Tarbiat Modares University protocols, which seek to optimize handling and minimize animal suffering. The guidelines, adopted from the Declaration of Helsinki (1975) and The Society for Neuroscience Animal Care and Use guidelines (1998), were approved for implementation by the Medical Ethics Committee, School of Medical Sciences of Tarbiat Modares University, on the 28th Farvardin, 1385/17th April, 2006 (Ghosi Mobaraki, Abedian Kenari, Bahrami Gorji, & Esmaeili, 2020; Safavi, Abedian Kenari, Tabarsa, & Esmaeili, 2019; Tazikeh, Abedian Kenari, & Esmaeili, 2019). After 1 day of starvation, fish were sampled and weighted to measure growth performance.…”
Section: Methodsmentioning
confidence: 99%
“…All procedures involving animals were performed according to the Tarbiat Modares University protocols, which seek to optimize handling and minimize animal suffering. The guidelines, adopted from the Declaration of Helsinki (1975) and The Society for Neuroscience Animal Care and Use guidelines (1998), were approved for implementation by the Medical Ethics Committee, School of Medical Sciences of Tarbiat Modares University, on the 28th Farvardin, 1385/17th April, 2006 (Ghosi Mobaraki, Abedian Kenari, Bahrami Gorji, & Esmaeili, 2020; Safavi, Abedian Kenari, Tabarsa, & Esmaeili, 2019; Tazikeh, Abedian Kenari, & Esmaeili, 2019). After 1 day of starvation, fish were sampled and weighted to measure growth performance.…”
Section: Methodsmentioning
confidence: 99%
“…Aquaculture has a high potential to provide food for humans in the next decades (Zaretabar et al, 2021). As the profitability of fish farming depends on growth performance and feed efficiency, any attitude towards improving these parameters can help increase sustainability (Asgari et al, 2020;Ghosi Mobaraki et al, 2020). An ideal diet for omnivorous fish species such as beluga (Huso huso) usually has 30%-40% fish meal and fish oil.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Fei et al (2020) reported that dietary amino acids could enhance sex steroid hormone synthesis and growth performance of yellow catfish, Pelteobagrus fulvidraco . Dietary manipulation also improved physiology of African Catfish, Clarias gariepinus (Al‐Deghayem & Suliman, 2019), pearl gourami, Trichogaster leeri (Ghosi Mobaraki, Abedian Kenari, Bahrami Gorji, & Esmaeili, 2020), red seabream, Pagrus major (M. S. Hossain et al, 2019), butter catfish, Ompok pabda (G. Chowdhury et al, 2020) and amberjack, Seriola dumerili (S. Hossain et al, 2018). However, the use of endocrine therapy and a nutritional management approach as potential thermal mitigation measures to support natural gametogenesis is still unexplored.…”
Section: Mitigation Measures For Fish During Extreme Temperature Eventsmentioning
confidence: 99%